Ecological land classification and mapping of Yazili canyon nature park in the mediterranean region, Turkey - Ozkan, Kursad; Mert, Ahmet (Journal of Environmental Engineering and Landscape Management, 2011)
Distinction of lands corresponding to hierarchical sequences of plant communities means hierarchical classification of ecosystems. In this context, it is essential in determining of effective environmental characteristics at each different hierarchic level of vegetation distinction. Thus, a hierarchical mapping including ecological land units can be provided owing to comparison of same hierarchical level of vegetation classes with the land units marked at the hierarchical level of the map. The study was carried out in order to classify and map hierarchically Yazili Canyon Nature Park situated in the Mediterranean region, Turkey. 107 sample plots were selected. TWINSPAN (the two-way indicator test) was applied in order to divide land into units, and chi-square tests were applied for confirmation of the units. Interspesific correlation analysis was also applied to determine the indicator species at each level of division. As a result, six portions were defined at different hierarchical levels in Yazili Canyon Nature Park. Climatic heterogeneity – which originated from the heterogeneous landscape structure of the canyon – plays an important role in this separation. Article in English. Ekologinis Turkijos viduržemio jūros regiono Yazili kanjono gamtinio parko žemių klasifikavimas ir kartografavimas Santrauka. Hierarchinis augalijos pasiskirstymas vietovėje lemia hierarchinę augalijos klasifikaciją. Svarbu nustatyti efektyvias aplinkos apsaugos charakteristikas kiekviename hierarchiniame augalijos lygmenyje. Tyrimas vyko siekiant atlikti hierarchinę ekosistemos klasifikaciją ir sukurti hierarchinį Turkijos Viduržemio jūros regiono Yazili kanjono gamtinio parko žemėlapį. Pasirinkta 107 ploteliai. Skirstant į tam tikrus vienetus, dviem būdais taikytas indikacinis testas (TWINSPAN), vienetai įvertinti pagal chi kvadrato testą. Abipusės koreliacijos būdu kiekviename lygmenyje nustatyta indikacinės rūšys. Pagal tai skirtinguose Yazili kanjono gamtinio parko hierarchiniuose lygiuose apibrėžtos šešios dalys. Skirstymui didelę įtaką turėjo tokio tipo vietovei būdingas klimato heterogeniškumas, kurį lemia kanjonui būdingas aplinkos heterogeniškumas. Reikšminiai žodžiai: TWINSPAN , hierarchinė ekosistemos klasifikacija, aplinkos heterogeniškumas, augalijos ir aplinkos sąsajos. Экологическая классификация земли и картография каньона Уазили внациональном парке средиземноморского региона Турции Резюме. Уникальность местности зависит от иерархического распределения растительности или иерархической классификации экосистемы. В этом контексте важно установить эффективные природоохранные характеристики для каждого иерархического уровня растительности. Настоящим исследованием преследовалась цель классифицировать экосистему и создать иерархическую карту каньона Уазили в Национальном парке Средиземноморского регионаТурции. Для этого были выбраны 107 участков. Два способа индикаторного теста TWINSPAN предназначалисьдля распределения по определенным единицам, а тест квадрата chi – для оценки этих единиц. Интерспецифическая корреляция была приспособлена для выявления индикаторных видов на каждом уровне. В результате былиустановлены шесть частей на разных иерархических уровнях каньона Уазили в Национальном парке. Гетерогенность ландшафтного климата, происходящая из характерного для каньона гетерогенного ландшафта, оказываетбольшое влияние на такое распределение. Ключевые слова: TWINSPAN, иерархическая классификация экосистемы, гетерогенность окружающей среды, взаимоотношения между растительностью и окружающей средой.